CORRELATION BETWEEN BODY MASS INDEX TOWARDS AGILITY FOOTBALL ATHLETES IN MELAWI REGENCY - Hidayat, Muhammad Yasir; Saraswati, Putu Ayu Sita; Widnyana, Made; Kinandana, Gede Parta (Sport and Fitness Journal, 2022)
Agility is used by soccer athletes when passing opponents by dribbling the ball in order to score goals more easily. Body Mass Index (BMI) affects agility. Athletes who have a normal BMI have better agility which is useful for displaying their maximum abilities. Athletes with an abnormal BMI can result in decreased agility and an increased risk of injury. This study aims to determine the correlation between BMI and agility in soccer athletes in Melawi Regency.This research is an analytic observational study with a cross sectional approach. The sample of this study amounted to 105 people who were selected using non-probability sampling technique with purposive sampling method. Agility was measured by t-test, while BMI was measured by the result of body weight () divided by the square of height () adjusted by category.Based on the non-parametric chi-square analysis test, the results were p = 0.021 (p<0.05) which indicates that there is a significant correlation between BMI and agility, where the lower the BMI, the higher the agility. This is because the higher the BMI causes an increase in the load that can inhibit muscle contraction.Based on the results of the study, it can be concluded that there is a significant correlation between body mass index and agility in soccer athletes in Melawi Regency. Keywords : Body Mass Index (BMI); agility; football athletes